Espinores de Weyl y el formalismo de helicidad - Díaz Cruz, J.L.; Larios, B.; Meza Aldama, O.; Reyes Pérez, J. (Revista Mexicana de Física E, 2015)
In this work we give a review of the original formulation of the relativistic wave equation for particles with spin one-half. Traditionally (Ã la Dirac), it’s proposed that the ``square root’’ of the Klein-Gordon (K-G) equation involves a 4 component (Dirac) spinor and in the non-relativistic limit it can be written as 2 equations for two 2 component spinors. On the other hand, there exists Weyl’s formalism, in which one works from the beginning with 2 component Weyl spinors, which are the fundamental objects of the helicity formalism. In this work we rederive Weyl’s equations directly, starting from K-G equation We also introduce the electromagnetic interaction with the Weyl spinors. As an example of the use of that formalism, we calculate Compton scattering using the helicity methods.